New Testament Interpretation as Performance - Barton, Stephen C. (Scottish journal of theology, 1999)
In recent study of the nature of NT interpretation, considerable attention in certain circles has been given to the possibility that there is one metaphor that is particularly appropriate for articulating what NT interpretation involves. It is the metaphor of performance. The purpose of this paper is to describe and develop this proposal and to give an assessment of it. To my knowledge, this is a task in biblical hermeneutics that has only just begun. If we ask why this is so, one possible answer lies in the fact that the proposal comes in the main from systematic and patristic theologians and therefore from outside the guild of biblical scholars. The consequence is that our customary division of labour inhibits us from attending with sufficient care to what our neighbours are saying even when it bears directly on our own work.